The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2355/isijinternational.45.1934
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Microstructural Factors to Hardness Change during Creep Exposure in Mod.9Cr-1Mo Steel

Abstract: The effect of microstructural factors on hardness was investigated in normalized, tempered, aged and crept materials for Mod.9Cr-1Mo steel, using nanoindentation and microhardness tests. Nanohardness and microhardness decreased during tempering, aging and creep exposure. Dislocation spacing, lath width, high angle boundary (block and packet boundary) spacing and inter-particle spacing increased during tempering, aging and creep exposure. A converted Vickers hardness was introduced to compare directly nanohardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…11a) is mainly associated with the decrease in the density of free dislocations (at constant subgrain size), and this is fully in line with our observations [16] and with previous work on the evolution of dislocation density during short-term creep [5]. Our results on the evolution of subgrain sizes agree well with results reported in the literature [22,23].…”
Section: Effects Associated With the Evolution Of Subgrainssupporting
confidence: 95%
See 3 more Smart Citations
“…11a) is mainly associated with the decrease in the density of free dislocations (at constant subgrain size), and this is fully in line with our observations [16] and with previous work on the evolution of dislocation density during short-term creep [5]. Our results on the evolution of subgrain sizes agree well with results reported in the literature [22,23].…”
Section: Effects Associated With the Evolution Of Subgrainssupporting
confidence: 95%
“…Carbides become mechanically important during creep [7], where they stabilize subgrain boundaries. Our results are also in line with a recent very careful assessment of microstructure of a 9% Cr tempered martensite ferritic steel (OIM and TEM) in combination with nano-, micro-and macrohardness measurements [22], where the strong decrease in room temperature hardness during long-term creep is mainly associated with subgrain coarsening. It was suggested [22] that the small decrease in hardness in the thread of the creep specimen (which we also observe in Fig.…”
Section: Effects Associated With the Evolution Of Subgrainssupporting
confidence: 92%
See 2 more Smart Citations
“…They were the decrease in dislocation density and coarsening of laths and/or subgrains rather than the decrease in solidsolution and precipitation strengthening, considering the relatively short creep times. However, Sawada et al [6] has revealed that lath boundaries have almost no influence on the strength mechanism in Mod.9Cr-1Mo steel. Therefore, the decrease in dislocation density seems to be the most significant factor of the decrease in Hm at the present test condition.…”
Section: Changes In Matrix Strength Due To Creepmentioning
confidence: 97%